Integrering av pelletsfabrik med Rya kraftvärmeverk i Göteborg : en teknisk och ekonomisk utredning - Abrahamsson, Charlotta (SLU/Dept. of Energy and Technology, 2008)
Göteborg Energi has a surplus of district heating during spring, summer and fall. The heat surplus is due to a constant production of waste heat from oil refineries and heat from waste incineration over the year. It would be desirable to increase the demand for heat and the uptime for the newly built combined heat and power generation plant, Rya Kraftvärmeverk. One alternative could be to integrate Rya Kraftvärmeverk with a pellet production facility. By producing heat, electricity and pellet in a joint process the energy use can be decreased. The production can also be more cost efficient due to a lower investment cost when using the same boiler etc, for different purposes.